Estimating the amount of British Columbia’s “big-treed” old growth: Navigating messy indicators - Price, Karen; Daust, Dave; Daust, Kiri; Holt, Rachel (Frontiers in Forests and Global Change, 2023)
British Columbia’s (BC) diverse forest ecosystems include highly productive old growth with global importance for carbon storage and biodiversity. Current estimates of the remaining amount of “big-treed” old growth vary tenfold, creating uncertainty that challenges provincial attempts to shift management policy towards ecological integrity. This uncertainty arises from using different remotely-sensed indicators and definitions of tree size. No ideal indicator exists. We attempt to improve clarity by evaluating the reliability of candidate indicators, calibrating selected indicators to improve consistency, and generating multiple estimates of big-treed old growth amount using calibrated indicators. To evaluate reliability, we compared inventory estimates of tree size and site productivity to measured tree size in 1 945 ground plots. Stand volume, tree density, basal area and diameter estimates performed poorly; we selected tree height and two measures of site productivity for further analysis. Estimated tree height best indicated current old growth size, followed by inventory-based site index and finally ecosystem-based site index. To assess the amount of big-treed old growth, we determined an equivalent “big” size threshold for each indicator, and calculated the area of old growth above the size threshold. The calibrated indicators agreed that very little remaining old growth supports large trees (1.5 – 3.3% for the biggest trees; 6 – 13% including medium sized trees that represent the largest growing in lower productivity interior ecosystems). Tree height cannot be used to compare the remaining area of big-treed old growth to the area expected naturally, an important input into ecological risk assessment and conservation planning, because height data are lost from the inventory after harvest. The two calibrated site productivity indicators agreed that the amount remaining is less than 30% of expected historical amount, posing high risk to biodiversity and resilience. We recommend using estimated height to identify the biggest remaining old growth stands for regional planning, and using calibrated inventory-based site index for risk assessment, until detailed ecosystem mapping has been verified to represent old growth variability. To reduce uncertainty, we suggest that planning groups compare several indicators and analysis approaches, adjusted to ensure equivalence, and use precaution to avoid unknowingly increasing risk.